FUNCTIONAL AND PSYCHOEMOTIONAL STATE OF SENIOR SCHOOL TEACHERS - Akhmadalieva N. O.; Iklasbayeva G. K. (Web of Journals Publishing, 2026)
The article is devoted to the analysis of the functional and psychoemotional state of senior school teachers in general education institutions. The factors influencing teachers’ health are examined, including workload, emotional burnout, stress, and working conditions. A review of modern studies focused on the psychoemotional and functional state of teachers, as well as the influence of microclimate, work schedules, and occupational risks, is presented. The study concludes that comprehensive preventive measures are necessary to preserve teachers’ health, including optimization of working conditions, psychological support, and monitoring of functional status.
Keywords: Functional state, psychoemotional state, senior school teacher, stress, emotional burnout, working conditions, work capacity, teachers’ health.